The Qur'anic Context and Its Impact on Interpretation: A Methodological Review of Contemporary Exegetes - Obada, Fadel; Ahmadnezhad, Amir; Sotoudehnia, Mohammadreza (Thi Qar Arts Journal, 2025)
Studying the Qur'anic context is one of the most important methodologies used in interpreting Qur'anic texts. Understanding the context contributes to providing accurate interpretations that align with the intended meaning of the verse or surah. In this regard, contemporary exegetes focus on studying various contexts of Qur'anic texts, such as linguistic, historical, and rhetorical contexts, to achieve interpretations that reflect contemporary reality and keep pace with developments in religious understanding.Modern studies show that context is not limited to the apparent meaning of the text but extends to include the circumstances surrounding the Qur'anic text and the developments of the era. This leads to deeper and more flexible interpretations of the texts, enhancing the understanding of Qur'anic verses in multiple temporal and spatial contexts. The Qur'anic context helps exegetes avoid partial interpretations that may deviate from the general purpose of the Qur'an.Through a methodological review of contemporary exegetes, it can be observed that there is a variation in how context is utilized in interpreting Qur'anic verses. While some exegetes primarily focus on the linguistic context, others prefer to emphasize the historical or social context to achieve interpretations more in line with contemporary developments. There is also a modern trend towards using contemporary critical and cognitive tools to understand Qur'anic texts, such as textual analysis and contextual understanding that intersects various sciences.Applying the contextual methodology in interpreting the Qur'an enhances our ability to understand Qur'anic texts in a more comprehensive and profound manner, helping to highlight the precise meanings and Qur'anic purposes that may be missed in superficial understanding of the texts. At the same time, this methodology forms a powerful tool for interacting with contemporary issues and the problems of the Islamic Ummah in a creative and renewed way.